Quantification of metals in macrophytes in an aquaculture area of the itaipu binational reservoir - Marengoni, Nilton Garcia; Chambo, Ana Paula Sartório (Scientia Agraria Paranaensis, 2021)
The macrophytes in natural conditions perform an important role in the maintenance and balance of aquatic environments with a capacity of absorbing the excess of nutrients and pollutants serving as bioindicators of water quality in aquatic ecosystems. The objective was to evaluate the levels of trace metals in three species of macrophytes (Egeria densa - submerged and Eichhornia crassipes and Salvinia auriculata - floating) collected around an aquaculture area of cages in the Itaipu Binational reservoir, during the four seasons of the year. The macrophyte samples were submitted of nitroperchloric digestion. Subsequently, the quantification of metals (Cu, Zn, Fe, Mn, Pb, Cd and Cr) was carried out by flame atomic absorption spectrometry analytical method. The concentration of Cu, Fe and Mn in E. densa and S. auriculata was higher (P<0.05) than in E. crassipes. The samples of S. auriculata and E. crassipes had the lowest concentrations (P<0.05) of Pb. The lowest metal pollution index (MPI) was determined in E. crassipes. There was greater bioaccumulation of metals in the root concerning the stem and leaves of E. crassipes (P<0.05). The results obtained in this study show the influence of seasonal variation in the levels of Fe and Zn and the species analyzed on the concentration of Fe, Zn and Mn accumulated in aquatic macrophytes. The macrophytes E. crassipes and E. densa can be considered efficient accumulators of metals, indicating the exposure of the concentration of trace metals around the aquaculture area intended for the fish production in cages.